ANALISIS FRAMINGBERITA HARIAN UMUM SOLOPOS TENTANG KESETARAAN KAUM DIFABEL PERIODE JANUARI-MARET 2012 - ., priyono (KOMUNITAS, 2014)
This research based on the author interest to issue equity interest. In real life there are many disability rights are not guaranteed to materialize despite a state regulation. While the role of the mass media or newspapers are still not optimal to voice disabilities equal rights as other citizens according to their needs. Object of this study is the Solopos news about the equality of disabled published during the period January to March 2012. Researched news are six items. The research aims to determine the framing of Solopos daily about disability equality. The research use framing analysis method with the analysis of Zhodang Pan and Gerald M. Kosicki. News that has been obtained in the data collection were analyzed by framing device of Pan Kosicki consisting of four major structures, namely syntax, script, thematic and rhetorical. Analysis results were then compared with the data results of interviews with the managing editor, desk editorand field reporter. The results showed Solopos view disabilities as an important issue. Disabled people deemed equalrights with other citizens according to their needs. Everything related disabilities equality rights have protrusion certain aspects such as the appearance of the dominant issues of disability equality and equality assertion supported sources in Solopos coverage.